2002
DOI: 10.1002/app.11263
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the compatibility of natural rubber/ethylene–propylene diene monomer rubber blends via natural rubber epoxidation

Abstract: ABSTRACT:The longitudinal ultrasonic velocity, longitudinal ultrasonic absorption (attenuation coefficient), glasstransition temperature, and Mooney viscosity for epoxidized natural rubber/ethylene-propylene diene monomer blends were measured. The variation of the longitudinal ultrasonic velocity with the blend ratios was linear, indicating a compatible system in comparison with the same system without epoxidation (natural rubber/ethylene-propylene diene monomer), which was incompatible. Also, the behavior was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Each of them has certain desirable physical and chemical properties which if combined in a blend would result in useful industrial products. Recently, Mounir, El-Sayed, and Afifi [4] epoxidized natural rubber and reported a compatible blend with EPDM. Methods determining the degree of compatibility have been reported, both theoretically and experimentally [5][6][7] .…”
Section: Introductionmentioning
confidence: 97%
“…Each of them has certain desirable physical and chemical properties which if combined in a blend would result in useful industrial products. Recently, Mounir, El-Sayed, and Afifi [4] epoxidized natural rubber and reported a compatible blend with EPDM. Methods determining the degree of compatibility have been reported, both theoretically and experimentally [5][6][7] .…”
Section: Introductionmentioning
confidence: 97%
“…The simple measurements of ultrasonic velocity reveal various aspects of the compatibility of polymer blends in both highly viscous and solid form. Sidkey et al [15,16] concluded that the presence of only one maximum for attenuation-composition curve reflects the Recently, Afifi et al [17,18] used the ultrasonic velocities and attenuation coefficient to study the compatibility of the epoxidized natural rubber-ethylene propylene diene monomer (ENR-EPDM) blends using pulse echo technique at a frequency of 2 MHz. The relation between ultrasonic velocity and composition showed a curvilinear type of S shape and a region of phase in version was shown.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic wave propagation for polymer characterization is a fast, nondestructive, and noninvasive technique based on low‐intensity ultrasound. The advantage of using ultrasound velocity measurements for investigating polymer compatibility has been shown by many workers 25–39. Ultrasound as a non‐destructive testing technique is normally associated with the detection of defects, cracking, pores etc.…”
Section: Introductionmentioning
confidence: 99%